Analysis of Road Drainage Capacity of Developing Industrial Area in Karawang - Amanda, Sely Audi; Sudjatmiko, Eddy Triyanto (President University, 2024)
Karawang district was formerly known as a rice barn in West Java. But now, this area has become one of Indonesia's largest industrial districts. Its great potential increases the community’s demand for business places. Therefore, the high activity of an area must be balanced with the fulfillment of infrastructure facilities. In maintaining adequate road conditions, it is necessary to provide an integrated drainage system between the road drainage system and the drainage system of the surrounding area. This paper is objective which is to evaluate the capacity and performance of existing road drainage channel. As the land use changes, it’s crucial to evaluate the increase rainfall water runoff. By collects and evaluating recent rainfall data and hydrological analysis using the Normal, Gumbel, Log Normal, and Log Pearson III methods to determine the design rainfall in South Karawang. The results of rain data processing obtained by the selected parameters test method are the Log Pearson III with 10-years of rainfall design 141.26 mm. After conducting capacity evaluation, the results show that the existing channels that serve the area (A) of 8.37 ha with the runoff coefficient (C) of 0.89 are needs to be increases to accommodate the surface rainfall water runoff discharge of, Q = 3.26 m3/s. Thus, a precast concrete U-Ditch of 1200 x 1400 mm will provide effective 400 mm of freeboard, W, and 0.5% as channel slope (s) is designed with channel discharge (Qchannel) of 3.39 m3/s to accommodate the needs of current conditions.